2022
DOI: 10.3389/fagro.2022.969960
|View full text |Cite
|
Sign up to set email alerts
|

The first report of chickpea (Cicer arietinum L.) tolerance to Paraquat in Australia

Abstract: Chickpea growers in Australia have no post-emergent (POST) herbicides labeled for broadleaf weed control and they rely on pre-emergent herbicides for control of broadleaf weeds. The objective of this study was to evaluate chickpea tolerance to POST application of paraquat (0, 90, 180, 360, and 540 g ai ha-1) in a randomized complete block design. Paraquat (180 g ai ha-1) applied POST (up to 10 days after crop emergence) did not injure chickpeas and reduce plant height, and biomass when compared with nontreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Recently, Mahajan et al [10] indicated that infestations of Avena ludoviciana Durieu and Argemone mexicana L. at densities of 15 and 17 plants m −2 caused an 83% and 48% reduction in chickpea yield, respectively, compared to weed-free conditions. Yield losses in chickpea may vary from 24% to 63%, depending on weed infestation levels [11]. However, when weeds are not effectively managed during the critical growth period of chickpea plants (35-60 days after emergence), yield losses as high as 88% [10] can be experienced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mahajan et al [10] indicated that infestations of Avena ludoviciana Durieu and Argemone mexicana L. at densities of 15 and 17 plants m −2 caused an 83% and 48% reduction in chickpea yield, respectively, compared to weed-free conditions. Yield losses in chickpea may vary from 24% to 63%, depending on weed infestation levels [11]. However, when weeds are not effectively managed during the critical growth period of chickpea plants (35-60 days after emergence), yield losses as high as 88% [10] can be experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Weed infestation adversely affects chickpea grain's dietary composition, particularly through a reduced nitrogen and crude protein content, thus compromising overall seed and grain quality [13]. Weeds compete for resources, impede nutrient uptake, and disrupt soil microbial activity, collectively diminishing chickpea's nutritional value [11,14]. Understanding the unique mechanisms by which weeds, particularly Asphodelus tenuifolius Cav., affect the dietary status of chickpea grain is of key importance to adopt efficient weed management strategies.…”
Section: Introductionmentioning
confidence: 99%